Investigation of microemulsion system for transdermal delivery of itraconazole - Arpan Chudasama; Vineetkumar Patel; Manish Nivsarkar; Kamala Vasu; Chamanlal Shishoo (Wolters Kluwer Medknow Publications, 2011)
A new oil-in-water microemulsion-based (ME) gel containing 1% itraconazole (ITZ) was developed for topical delivery. The solubility of ITZ in oils and surfactants was evaluated to identify potential excipients. The microemulsion existence ranges were defined through the construction of the pseudoternary phase diagrams. The optimized microemulsion was characterized for its morphology and particle size distribution. The optimized microemulsion was incorporated into polymeric gels of Lutrol F127, Xanthan gum, and Carbopol 934 for convenient application and evaluated for pH, drug content, viscosity, and spreadability. In vitro drug permeation of ME gels was determined across excised rat skins. Furthermore, in vitro antimycotic inhibitory activity of the gels was conducted using agar-cup method and Candida albicans as a test organism. The droplet size of the optimized microemulsion was found to be <100 nm. The optimized Lutrol F 127 ME gel showed pH in the range of 5.68΁0.02 and spreadability of 5.75΁1.396 gcm/s. The viscosity of ME gel was found to be 1805.535΁542.4 mPa s. The permeation rate (flux) of ITZ from prepared ME gel was found to be 4.234 ΅g/cm/h. The release profile exhibited diffusion controlled mechanism of drug release from ME ITZ gel. The developed ME gels were nonirritant and there was no erythema or edema. The antifungal activity of ITZ showed the widest zone of inhibition with Lutrol F127 ME gel. These results indicate that the studied ME gel may be a promising vehicle for topical delivery of ITZ.